Evaluation of body weight-based vancomycin therapy and the incidence of nephrotoxicity: a retrospective study in the northwest of China. (August 2015) - Dong, Mo-Han; Wang, Jing-Wen; Wu, Yin; Chen, Bei-Yu; Yu, Min; Wen, Ai-Dong
Highlights: Associations between vancomycin treatment and nephrotoxicity were evaluated retrospectively in 90 patients in the northwest of China. Fourteen (15.6%) patients developed nephrotoxicity, with serum creatinine elevated significantly from mean (standard deviation) 90.0 (18.8) μmol/l to 133.8 (63.2) μmol/l ( p = 0.015). Drug dosing >38 mg/kg/day and a serum trough level >20 mg/l were identified as risk factors of nephrotoxicity. The renal function of critically ill patients receiving vancomycin should be monitored closely. Summary: Objective: To identify specific risk factors of vancomycin-induced nephrotoxicity in China, as the relationship between vancomycin therapy (dosing and trough concentration monitoring) and nephrotoxicity has been the subject of critical debate. Methods: The cases of 90 critically ill patients who received vancomycin therapy in Xijing Hospital in the northwest of China between March 2014 and January 2015 were reviewed retrospectively. Vancomycin dosing, blood serum trough concentration, and other independent risk factors associated with nephrotoxicity were evaluated in a multivariable model. Results: Among the 90 critically ill patients, 59 were males; mean age was 46.3 years. The indications for vancomycin use were methicillin-resistant Staphylococcus aureus -associated pneumonia, central nervous system infection, and bacteremia. Clinical pharmacists prescribed weight-based dosing, ranging from 20 to 45 mg/kg/day. Fourteen (15.6%) patients developed nephrotoxicity, with serum creatinine elevated significantly from a mean (standard deviation) of 90.0 (18.8) μmol/l to 133.8 (63.2) μmol/l ( p = 0.015). It was found that those with a vancomycin dosage >38 mg/kg/day (50.0% vs. 11.3%, p = 0.004) and a vancomycin serum trough concentration >20 mg/l (57.1% vs. 12.0%, p = 0.01) were more likely to develop nephrotoxicity. Conclusion: The data from this study indicate that a vancomycin dosage >38 mg/kg/day and a serum trough level >20 mg/l are both independent factors associated with the development of nephrotoxicity, suggesting that renal function should be monitored closely during vancomycin treatment.